ANALISIS USAHA TANI BUDIDAYA TANAMAN JAGUNG DI DESA BOCOR, KECAMATAN BULUSPESANTREN KABUPATEN KEBUMEN - Riski Utomo; Umi Barokah; Aulia Rahmawati (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
This study aims to determine (1) the amount of income and income of farmers in the cultivation of corn during one growing season, (2) the amount of R/C of corn business in one growing season. This is done because many farmers have not done farming analysis to find out the profit or loss of corn cultivation starting from the cost of cultivation support equipment, the cost of production facilities, and the cost of the required labor. Farmers in Bocor Village, Buluspeseantren Sub-district, Kebumen Regency, especially in upland areas are able to plant two planting seasons in one year. Moreover, in recent years the selling price of dry shelled corn has been able to penetrate the price of 5000/kg. This research was conducted by interview method directly to one corn farmer. This interview was conducted with the aim of obtaining real data about the costs needed by farmers to cultivate corn in one growing season. The results of this study indicate that the total cost for one planting season is Rp. 20,445,002, - for revenue of Rp. 39,150,000, - so that the income value is Rp. 18,704,978. The amount of R/C in corn farming once a planting season per hectare is 1.91, meaning that for every Rp. 1,- the costs incurred will receive an income of Rp. 1.91,- and an income of Rp. 0.91.-. The analysis of the corn cultivation business shows that the farming is profitable and feasible because the R/C > 1 is 1.91. Keywords: Cultivation, Corn, Capital